2014
DOI: 10.1080/10826068.2014.940966
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Medium Composition for Erythritol Production from Glycerol byYarrowia lipolyticaUsing Response Surface Methodology

Abstract: Several factors affecting erythritol production from glycerol by Yarrowia lipolytica Wratislavia K1 strain were examined in batch fermentations. Ammonium sulfate, monopotassium phosphate, and sodium chloride were identified as critical medium components that determine the ratio of polyols produced. The central composite rotatable experimental design was used to optimize medium composition for erythritol production. The concentrations of ammonium sulfate, monopotassium phosphate, and sodium chloride in the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…Among the research groups involved in these projects, the Rymowicz group has made a lot of progress in polyalcohol production from Y. lipolytica using glycerol as a carbon source (Rymowicz et al, 2008(Rymowicz et al, , 2010Rywińska et al, 2009Rywińska et al, , 2010bRywińska et al, , 2010cRywińska et al, , 2015. Generally, erythritol was produced with citric acid production from wild-type and mutant Y. lipolytica strains using glycerol as a carbon source.…”
Section: Othersmentioning
confidence: 98%
See 1 more Smart Citation
“…Among the research groups involved in these projects, the Rymowicz group has made a lot of progress in polyalcohol production from Y. lipolytica using glycerol as a carbon source (Rymowicz et al, 2008(Rymowicz et al, , 2010Rywińska et al, 2009Rywińska et al, , 2010bRywińska et al, , 2010cRywińska et al, , 2015. Generally, erythritol was produced with citric acid production from wild-type and mutant Y. lipolytica strains using glycerol as a carbon source.…”
Section: Othersmentioning
confidence: 98%
“…Rymowicz et al (2009) optimized the fermentation process, and 170 g/L of erythritol was produced by mutant Y. lipolytica Wratislavia K1 in a fed-batch culture with raw glycerol as the sole carbon source, while no citric acid was obtained under the same conditions. Naturally, erythritol productivity is affected by various factors, such as the culture mode, agitation rate and osmotic pressure (Tomaszewska et al, 2012;Rywińska et al, 2013bRywińska et al, , 2015Tomaszewska et al, 2014). Mirończuk et al (2014) developed the fed-batch culture mode for erythritol production.…”
Section: Othersmentioning
confidence: 99%
“…In this case, KH 2 PO 4 and MgSO 4 concentrations were not found to be significant, unlike glucose and ammonium sulphate concentration, while pH had a significant impact on erythritol production (Ghezelbash, Nahvi, & Emamzadeh, ). In contrast, other studies on Y. lipolytica identified KH 2 PO 4 as a key parameter in erythritol synthesis, in addition to glycerol, ammonium sulphate, NaCl and urea (Rywińska et al, ; Yang et al, ). In Aureobasidium pullulans , the key parameters were identified as yeast extract, KH 2 PO 4 and citric acid concentrations (Guo, Li, Chen, Guo, & Xiao, ).…”
Section: Optimization Of Erythritol Productionmentioning
confidence: 87%
“…The nature of the nitrogen source and its concentration are important parameters, although varying results were obtained regarding the optimal conditions. In Y. lipolytica , some studies found organic nitrogen sources such as yeast extract to be the most suitable for erythritol production (Tomaszewska, Rywińska, & Rymowicz, ) while others yielded better results with inorganic nitrogen sources such as ammonium sulphate (Ghezelbash, Nahvi, & Emamzadeh, ; Rakicka, Rukowicz, Rywińska, Lazar, & Rymowicz, ; Rywińska, Marcinkiewicz, Cibis, & Rymowicz, ). In P. tsukubaensis , the nature of nitrogen source had a remarkable impact on erythritol productivity and yield.…”
Section: Optimization Of Erythritol Productionmentioning
confidence: 99%
“…Various factors aff ecting fermentation have been examined, e.g. diff erent cultivation systems, type of substrate, and addition of salt or supplementation with minerals (9,(11)(12)(13)(14)(15). Up to now, the batch, fed-batch or repeated--batch cultures have been tested for erythritol biosynthesis from glycerol (9,13).…”
Section: Introductionmentioning
confidence: 99%